Island of Reil (Insula) in the Human Brain Anatomical, Functional, Clinical and Surgical Aspects (Springer International Publishing, 2018)
This book provides an in-depth review of the insula, with emphasis on anatomical, diagnostics, clinical, and surgical features. The insular cortex is involved in a variety of functions, but a comprehensive resource cataloging these functions is not available in the current literature. This book gathers highly informative chapters written and edited by leading international authorities in the field and covers the full range of the insular cortex, approaching it in four main sections: firstly, the embryology and anatomy of the human insula; secondly, the functions of the human insula, including its role in nociception, language, decision making, cognition, emotional awareness etc.; thirdly, clinical disorders related to the insula such as epilepsy, schizophrenia, and Parkinson's disease; and fourthly, surgical techniques for insular gliomas and temporal lobe epilepsy. This comprehensive reference book will be an ideal source for neurosurgeons, neurologists and neuroanatomists seeking both basic and more advanced information regarding this unique structure in the human brain.